The effects of the nanoselenium supplementation to the production parameters and the selenium retention of the red drum (Sciaenops ocellatus) - Juhász, Péter; Fehér, Milan; Csorvasi, Éva; Bársony, Péter; Remenyik, Judit; Sztrik, Attila; Prokisch, József; Stündl, László (Acta Agraria Debreceniensis, 2014)
The selenium is an essential trace element with antioxidant effect, constituent of many enzymes, natural component of the body of the animals. The addition to the fish feed as micro element supplementation is generally accepted. Numerous animal experiments veryfied, that the antioxidant effect of the nanoselenium is higher than other selenium forms. But no much information is available of the usuage at fish.In the experiment were investigated the effects of the nanoselenium supplementation of a commercial fish feed were investigated to the production parameters and the body tissue composition. The correlation between the accumulated selenium content of the body and the treatment, and the feed conversation was also statistically analyzed beside the production parameters. Furthermore we were curious, if can be toxic the nanoselenium in higher doses.The experimental stock was placed into 12 plastic tanks (each 70 l water vol.) in a recirculation system for larval rearing. The salinity and the water temperature was constant during the 8 week long experiment. The feeding was ad libitum, 4 times a day. Beside the control five (1, 1.5, 2.5, 5.5, 10.5 mg Se kg-1) duplicated treatment were set.According to the results, from the production parameters only at the value of FCR and the survival was found significant difference (p